Evidence for water-assisted diffusion creep in the mylonitic gneisses of Giuncana, northern Sardinia, Italy - Casini, L.; Senserini, P.; Oggiano, G. (TRABAJOS DE GEOLOGÍA, 2009)
Quartz ribbons in Variscan, water-rich, amphibolite facies (580-635 ºC; 6.5-7 kbar) mylonitic paragneisses from the Giuncana-Badesi shear zone (GBsz), north Sardinia, Italy, preserve recrystallized grain-size on the millimetre-scale, with lobate/cuspate quartz-feldspar phase boundaries. Feldspars cusps preferentially develop at foliation-perpendicular phase boundaries, strongly aligned with the inferred direction of finite extension. This microstructure is significantly different from the coeval, water-deficient, migmatite mylonites observed along the GBsz around Badesi, where a fine, dynamically recrystallized, quartz-feldspar matrix wraps around sigmoidal feldspar porphyroclasts. This difference indicates that the strain-induced recrystallization mechanism in migmatite mylonites is progressive subgrain-rotation bulging, whereas in paragneiss mylonites the dominant recrystallization mechanism is grain boundary migration coupled with diffusional creep. The volume diffusion localized within quartz ribbons, where feldspars are consumed at quartz-feldspar foliation-parallel boundaries, and growth at quartz-feldspar-quartz foliation-perpendicular boundaries. Both mylonites experienced similar PT conditions during deformation; however the dominant recrystallization mechanism is different. The presence of an H2O-rich fluids environment in the paragneiss mylonites strongly reflects the switch from dislocation to diffusional creep; hence we suggest that such local fluctuation of water may trigger volume diffusion at unusually low-T.